Application of emulsified acids on sandstone formation at elevated temperature conditions: an experimental study - Shafiq, M.; Chong, Y.; Ben Mahmud, Hisham; Hossain, Mofazzal; Rezaee, M. Reza; Testamanti, N. (SpringerOpen, 2018)
Emulsified acid has attracted considerable attention of the oil and gas industry due to its delayed nature that allows deeper penetration of acid into the formation which essentially facilitate further enhancing the well productivity, and at the same time minimizes the corrosion issues. However, emulsified acid has only been extensively studied and applied on carbonate formations. Considering more than half of the reservoirs worldwide are sandstone reservoirs, studying the effects of emulsified acid on sandstone under high-temperature conditions would unlock the potential of emulsified acid and help generate more value for the oil and gas industry by improving the well productivity from sandstone reservoirs. To ensure the applicability of the emulsified acid on the real sandstone reservoir, which usually has a temperature higher than ambient conditions, the stability of emulsified acids is investigated under 300 °F. Then, the stable emulsified acid samples are developed and their impact on the properties of Berea sandstone core samples, including porosity, pore-size distribution, permeability and wettability, are investigated. The core samples have undergone pre-flush (10% HCl:5% CH3COOH) before the main flush (emulsified acid). The emulsified acids are prepared using hydrofluoric acid, hydrochloric acid, phosphoric acid, cationic surfactant and chelating agent. Fourteen core samples are saturated with different emulsified acids under vacuum conditions for 3 days to ensure maximum saturation. The porosity, permeability and wettability of each core sample are measured before and after the reaction with acid. Nuclear magnetic resonance analysis has been applied to evaluate the change in pore size distribution. This study has demonstrated that the emulsified acids are capable of improving the porosity and permeability of Berea sandstone core sample. The pore size distribution has also been affected by the application of emulsified acid, where more large pores have been evolved to the core samples due to the reaction of acids with the sandstone which ultimately helps in improving the productivity of hydrocarbons. This indicates less precipitation of the secondary reaction products resulting better enhancement in sandstone flow properties. These results demonstrate the potential of emulsified acid during sandstone acidizing as emulsified acid significantly improved the sandstone properties which can essentially enhance the well productivity.